Border Police Procedure in the Case of Smuggling of Weapons and Military Equipment (Kriminalističke teme, 2018)
Reason for writing and research problem(s): Possession of illegal weapons, explosives and any other equipment that is not under the control of the government and the administration of any state is a jolt for both terrorist activities and other serious offenses related to trafficking in narcotics, people and organized crime. Officers of the Border Police are at the first level of defense, and to prevent the introduction of illegal firearms in Bosnia and Herzegovina as well as the release of the same.Aims of the paper: The goal of this work is to elaborate a detailed procedure for the conduct of authorized officials of the Border Police, according to positive laws in Bosnia and Herzegovina, with the aim of detecting and recognizing perpetrators, as well as procedures in case of illegal weapon detection during the control of bureaucracy at border crossings.Methodology: Analysis of legal document. This allows the application of practice content and the steps of acting according to standard operating procedures.Research/Paper Limitation: The research will focus on events and situations related to the work of border police in case of firearms engagement when conducting border control.Results / General Conclusion: Certain situations of smuggling firearms, explosive materials and other equipment, as well as investigations, resulted in the development of standard operational procedures, which have been elaborated in detail in this work. In this way, the procedures and order of the procedures necessary to prove the existence of the criminal offense have been elaborated in detail, and the case in court has been completed by a conviction.Research / Paper Validity: Such analysis and research so far have not been done in our country. However, within the framework of the SALW rolling strategy in Bosnia and Herzegovina, methods and procedures for the identification and handling of weapons are being developed. The basic feature and goal is to determine the weapon's movement line, or its ultimate legal owner. This contributes to the proper handling of border police officers in the conduct of daily activities, detection and recognition of firearms smugglers and explosives.